Vaccine Hesitancy among Caregivers of Children Attending Immunization Clinic at Gwalior in Central India - Prashant Kumar Dixit; Mahendra Chouksey; Richa Changulani; Durgesh Shukla (RGUHS Journal of Nursing Sciences)
Background Even though majority of parents vaccinate their children vaccine hesitancy VH has grown in popularity. It is unclear how this vaccination reluctance culture came to be and how it affects parents decisions regarding immunization schedule.Objectives The present study was conducted to identify the socio-economic and demographic subgroups and to explore the reasons of vaccine hesitancy among caregivers of children attending immunization clinic.Methods The present cross-sectional study was conducted at the immunization clinic of a tertiary care center at GR Medical College Gwalior MP India. In the present study 450 caregivers were included and the socioeconomic status vaccine hesitancy VH and reasons for VH were assessed. Statistical tests like Chi square test and Logistic regression were applied. Frequency percentage odds ratio OR with their respective 95 confidence interval were calculated and p value lt0.05 was considered as statistically significant.Results In total vaccine hesitancy was observed among the 103 22.9 caregivers. Occupation of father business 26.09 others like farmerdaily wage worker 35.90 socio-economic status of the family middle class 33.02 lower middle class 35.59 SC-ST caste category 31.25 illiterate mother 46.67 illiterate father 40.0 were found to be significantly related to VH. Illiterate mothers were about four times at higher risk OR 4.247 95 CI 1.459-12.365 as compared to highly educated graduate and above mothers. Caregivers visiting for fourth vaccination 38.04 of their children were found to have high VH. Sickness of the child 40.8 was reported to be the most common reason for VH followed by No caregiver available to accompany the child 16.5 Lack of awareness of vaccination schedule 16.5 Forgot date 15.5 and reluctance 10.7.Conclusion The vaccine hesitancy was prevalent among the caregivers. To ensure full immunization for the children it is vital to raise awareness among newlywed couples and pregnant women.